STUDENTS’ DIFFICULTIES IN COMPREHENDING NARRATIVE TEXT AT THE ELEVENTH GRADE OF SMA SWASTA FAJARMAS BAWONAURU - Nasimanis Zebua; Rebecca Evelyn Laiya; Restu Damai Laia (Universitas Nias Raya, 2022)
This research aimed at analysing the difficulties incomprehending narrative text at the eleventh grade of SMA Swasta Fajarmas Bawonauru. This research designed by using qualitative descriptive method. In analyzing the data, the researcher used theory of Miles and Huberman; data reduction, data display, and conclusion drawing/verification. The data source of this study was taken from the Eleventh Grade of SMA Swasta Fajarmas Bawonauru. To get the data, researcher use Documentation and Interview technique. The data of this study are difficulties and factors. To examine the credibility of this study the researcher used triangulation. The results of this study found that there were 5difficulties that is (1) Difficulties understanding the meaning of text that given by teacher in the classroom, (2) Difficulties in understanding new words, (3) Difficulties in understanding the purpose of the text, (4) Difficulties in understand language feature of narrative text, (5) Difficulties in understanding grammar in narrative textand factors were 2 that is (1) Limited vocabulary, (2) Teacher explanationthat occurred at Eleventh Grade of SMA Swasta Fajarmas Bawonauru.